Analisis Model Struktural Hubungan Pelatihan, Pemberdayaan, Kepuasan Kerja dan Kinerja Karyawan - Meilan Sugiarto; Marni Ningsih; Lukmono Hadi (Jurnal Administrasi Bisnis, 2020)
Employee performance has a crucial and decisive role in achieving an organization's success. This research conducted at PT. Madubaru Yogyakarta to investigate the impact of training that employees have participated in and empowerment on performance mediated by job satisfaction. Fifty employees of PT. Madubaru Yogyakarta used as a sample during this study. Data analysis and hypothesis testing using SEM-PLS 3.2.8. This study found that training that had been attended by employees and empowerment had a significant positive effect on performance, yet as on job satisfaction. Job satisfaction alone features a significant positive impact on performance. Indirectly, job satisfaction is in a position to mediate the effect of training and individual empowerment on indirect performance, and the indirect effect is essential and decisive. PT. Madubaru Yogyakarta is suggested within the use of coaching methods to be more accurate in order to achieve the training objectives and therefore the direction of employee empowerment is more emphasized on improving performance instead of merely increasing employee satisfaction at work. Realize the targets set by the corporate within the future, the amount of employee satisfaction at work and current performance still has to be improved in order that employee contributions recover.